KAJIAN KEBAHASAAN PADA IKLAN CETAK DI MASA PANDEMI COVID-19 - Vilya Lakstian Catra Mulia (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2020)
Covid-19 epidemic attacked Indonesia so that the government decided policy to have to stay at home which started in the middle of March 2020. People had to adapt to the situation. This moment attracts the attention of service and product providers to conform. The researcher uses printed advertisements as the data source in the form of a multimodal document and find various businesses respond to the condition. They support the government’s policy while remaining motivating customers to use their products and services. The research is done in a qualitative paradigm towards words, phrases, clauses, sentences, and pictures as the data to answer the research topic. The data source was taken from the daily newspaper Kompas at the beginning of staying at home policy implementation by the government. The data collection was done by criterion-based sampling. Supported by the multimodal analysis approach, this research observes how linguistic and visual image components simultaneously convey intentions of the advertisements in the pandemic outbreaks. Readers are directed to know various terms raised by the advertisement to campaign the government’s policy while remain promoting. The researcher finds kinds of text genres working harmoniously with visual images to articulate meanings. This research is able to show that offered products and services by providers in their pandemic-time advertisement are part of the solution towards customers’ needs while physical and social distancings were enforced. Linguistic analysis in this research gives new findings of the benefit of text and visual images to express meanings in various ways for the same goal.Wabah Covid-19 melanda Indonesia sehingga pemerintah menetapkan kebijakan untuk beraktivitas di rumah saja mulai pertengahan bulan Maret 2020. Masyarakat harus bisa beradaptasi dengan situasi. Momen ini turut menarik perhatian penyedia layanan jasa dan produk untuk menyesuaikan diri. Peneliti menggunakan iklan cetak sebagai sumber data berupa dokumen multimodal dan menemukan beragam perusahaanturut merespon keadaan ini. Mereka mendukung kebijakan pemerintahsambil tetap mendorong konsumen untuk menggunakan produk dan jasa yang dimiliki. Penelitian dilakukan dengan paradigma kualitatif terhadap kata, frasa, klausa, kalimat, dan gambar sebagai data untuk menjawab topik penelitian. Sumber data diperoleh dari koran harian Kompas pada awal masa berlakunya kebijakan aktivitas di rumah oleh pemerintah. Pengumpulan data dilakukan dengan teknik sampling berbasis kriteria. Didukung dengan pendekatan analisis dokumen multimodal, penelitian ini mengamati bagaimana komponen linguistik dan visual secara simultan menyampaikan maksud dari beragam iklan tersebut di saat pandemi. Pembaca diarahkan untuk mengetahui beragam istilah yang diangkat oleh iklan-iklan itu untuk mengampanyekan kebijakan pemerintah sambil tetap promosi. Peneliti menemukan macam-macamgenreteks yang berjalan harmonis dengan tampilan visual untuk mengartikulasikan makna. Penelitian ini mampu menunjukkan bahwa produk dan jasa yang ditawarkan perusahan pada iklan di masa pandemi merupakan bagian dari solusi terhadap kebutuhan konsumen saat jarak fisik dan sosial diberlakukan. Analisis kebahasaan dalam penelitian ini memberikan temuan baru tentang manfaat teks dan tampilan visual untuk menyuarakan maksud dengan beragam cara untuk tujuan yang sama.